Special education classrooms, language, and space : a discursive-linguistic reflection - Caetano, Carmem Jená Machado (2014)
Originating from the notion of space and language as formulated by Gunn (2002) and based on the theoretical foundation of Critical Discourse Analysis, as proposed by Norman Fairclough (2003), this paper deals with the investigation of identity (re)construction for teachers in special education classrooms in Brazil. Elements from Fairclough’s theory are used to approach the category of space in language praxis for the purpose of investigating, specifically, how people involved in the social events of special education represent this social space and how issues of power and ideology are perceived in the discourse (s) of this education assistant model.